PENGARUH DISIPLIN KERJA, KEPUASAN KERJA DAN MOTIVASI PRESTASI TERHADAP KOMITMEN ORGANISASI PADA PUSKESMAS BANTAR GEBANG BEKASI - Luthfurrahman Luthfurrahman; Meita Pragiwani (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2026)
This research employed a quantitative approach with a descriptive research strategy and an associative design. The population consisted of all 60 employees of Puskesmas Bantar Gebang Bekasi. Using a random sampling technique, the entire population was included as the research sample. The data used were primary data collected through questionnaires distributed via Google Form. Statistical analysis was conducted to test the proposed hypotheses. The results indicate that Work Discipline does not have a significant effect on Organizational Commitment. Job Satisfaction has a positive and significant effect on Organizational Commitment. Meanwhile, Achievement Motivation does not have a significant effect on Organizational Commitment. These findings suggest that Job Satisfaction is the most influential factor in strengthening Organizational Commitment among employees of Puskesmas Bantar Gebang Bekasi. Therefore, improving job satisfaction through a better work environment, leadership support, and a fair reward system can serve as an effective managerial strategy to enhance employees’ organizational commitment